Evaluasi Penggunaan Antibiotik pada Pasien Pneumonia di Rumah Sakit X Kota Malang - Magdalena Tania Tnesi; Agung Permata; Rakhmadani Gadis Aprilianti; Jessica Choirunniswah (Indonesian Journal of Pharmaceutical Education, 2023)
Pneumonia is an infection that occurs at the end of the bronchi and alveoli caused by bacteria, fungi, viruses or parasites. This disease is an inflammatory infection that usually consists of a cough and runny nose along with shortness of breath or an increase in the respiratory rate becoming faster. All ages are often affected by this condition, but toddlers are more often affected. One way to treat pneumonia is to use antibiotics, where resistance often occurs if not monitored properly. The aim of this research is to examine the use of the Gyssens technique in accordance with the Republic of Indonesia Minister of Health Regulation No. 8 of 2015 for the use of antibiotics in pneumonia patients at X Hospital, Malang. This type of research is non-experimental qualitative with a descriptive design with a retrospective data collection method. In this research, a purposive sample method was used for the sampling process. The sample used was 80 people. Based on research findings, 95% (76 cases) of antibiotics were given correctly, while only 5% (4 cases) of antibiotics were used incorrectly.